(untitled) (Medical Forum Monthly, 2024)
Objective: To assess whether testing serum PSA levels ranging from 10 to 4 ng/ml is more effective in detecting prostate cancer compared to measuring serum PSA levels between 20 and 10 ng/ml. Study Design: A prospective comparative study Place and Duration of Study: This study was conducted at the Pakistan Railway Hospital, Rawalpindi from June 2022 to December 2022. Methods: This research involved a comparison among 114 males aged 50 years and above who experienced symptoms related to their lower urinary tract. These individuals were separated into two categories depending on their serum PSA levels, which were determined during the diagnosis process. In Group A, Patients exhibited PSA levels ranging from 10 - 4 ng/ml. While Group B included individuals whose PSA levels ranged from 20 -10 ng/ml. Before taking part in the study, all participants gave their consent in writing. Prostate biopsies were conducted in both groups and prostate cancer incidence was compared. Results: The average age of the patients was 68.56±4.80 years. Common symptoms reported included urgent urination (26.32%), increased urinary frequency (32.46%), and urination at night (38.60%), weak stream (25.44%), urinary leakage (22.81%), and hematuria (6.14%). Upon examination, findings from digital rectal examination (DRE) showed a lump (30.84%), firm hardness (29.82%), median sulcus obliteration (32.46%), and non-symmetry (22.81%). Both groups studied had similar mean age and occurrences of various lower urinary tract symptoms (LUTS) and DRE findings. The second group (Group-B) demonstrated notably higher average levels of serum prostate-specific antigen (1596±2.72 ng/ml compared to 5.09±1.60 ng/ml; p<0.001), along with greater pre-void (528±94 ml vs. 461±92 ml; p<0.001) and post-void residual volumes (212±56 ml vs. 102±55 ml; p<0.001) in contrast to the initial group (Group-A). Prostate cancer was diagnosed in 28 (24.56%) patients, with the occurrence rate notably higher in Group B (33.33% vs. 15.79%; p=0.029) than in Group A. Conclusion: PSA levels in the blood can indicate the presence of malignant prostate tissue. This means that if the PSA level is high, it is important to examine the tissue to exclude the possibility of cancer. Studies have shown that there is a relationship between elevated PSA levels at the time of biopsy and an increased incidence of prostate cancer. Therefore, it is recommended to keep an eye on the PSA level and seek medical advice if it is higher than normal.